Placental Dysfunction and Fetal Programming: The Importance of Placental Size, Shape, Histopathology, and Molecular Composition - Longtine, Mark S. (2011)
Normal function of the placenta is pivotal for optimal fetal growth and development. Fetal programming commonly is associated with placental dysfunction that predisposes to obstetric complications and .suboptimal fetal outcomes. We consider several clinical phenotypes for placental dysfunction that likely predispose to fetal programming. Some of these reflect abnormal development of the chorioallantoic placenta in size, shape, or histopathology. Others result when exogenous stressors in the maternal environment combine with maladaptation of the placental response to yield small placentas with limited reserve, as typical of early-onset intrauterine growth restriction and preeclampsia. Still others reflect epigenetic changes, including altered expression of imprinted genes, altered enzymatic activity, or altered efficiencies in nutrient transport. Although the human placenta is a transient organ that persists only 9 months, the effects of this organ on the offspring remain for a lifetime.